<span>9596.92898273, i put this in my calc. hope this helps!</span>
Answer:
y=y(.11y+8)
Step-by-step explanation:
One nice thing about this situation is that you’ve been given everything in the same base. To review a little on the laws of exponents, when you have two exponents with the same base being:
– Multiplied: Add their exponents
– Divided: Subtract their exponents
We can see that in both the numerator and denominator we have exponents *multiplied* together, and the product in the numerator is being *divided* by the product in the detonator, so that translates to *summing the exponents on the top and bottom and then finding their difference*. Let’s throw away the twos for a moment and just focus on the exponents. We have
[11/2 + (-7) + (-5)] - [3 + 1/2 + (-10)]
For convenience’s sake, I’m going to turn 11/2 into the mixed number 5 1/2. Summing the terms in the first brackets gives us
5 1/2 + (-7) + (-5) = - 1 1/2 + (-5) = -6 1/2
And summing the terms in the second:
3 + 1/2 + (-10) = 3 1/2 + (-10) = -6 1/2
Putting those both into our first question gives us -6 1/2 - (-6 1/2), which is 0, since any number minus itself gives us 0.
Now we can bring the 2 back into the mix. The 0 we found is the exponent the 2 is being raised to, so our answer is
2^0, which is just 1.
By ASA postulate it can be say that the triangle ABC and triangle MRQ are congruent
<h3>What is Angle Sum Property?</h3>
The sum of all three angles(interior) of a triangle is 180 degrees, and the exterior angle of a triangle measures the same as the sum of its two opposite interior angles.
Using Angle Sum Property, in ΔMRQ
<M + <R + <Q= 180
<M + 42 + 85 = 180
<M = 180 -42
<M= 53°
Now, In ΔMRQ and ΔABC
<A= <R ,
<B = <M
AB = MR
Hence, By ASA criteria ΔMRQ ≅ ΔABC
Learn more about this concept here:
brainly.com/question/3486366
#SPJ1
You have to distribute the parentheses first. Since there is a negative sign in front of the parentheses, it counts as a negative 1. After you distribute you should get: -5+6x=20x+12, but that is not your final answer. After you add like terms: 17x=-17. Divide 17 on both sides: x=-1. X=-1 is your final answer.